Fast Trajectory Planning for VGT Manipulator via Convex Optimization. (30th September 2015) - Yang, Yongsheng; Jiang, Bosen; Hu, Shiqiang
Variable-geometry truss (VGT) can be used as joints in a large, lightweight, high load-bearing manipulator for many industrial applications. This paper introduces the modelling process of a multisection three-degree-freedom double octahedral VGT manipulator and proposes a new point-to-point trajectory planning algorithm for a VGT manipulator with a nonlinear convex optimization approach. The trajectory planning problem is converted to a quadratic convex optimization problem, and if some parameters are appropriately chosen the proposed algorithm is proved to be of global convergence and to have a super-linear convergence rate. The effectiveness of the proposed algorithm is illustrated by numerical simulation.